2018
DOI: 10.1186/s12957-018-1336-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of lateral lymph node metastasis in cN0 papillary thyroid carcinoma

Abstract: BackgroundCervical lymph node metastasis of papillary thyroid carcinoma (PTC) is common. However, whether undergoing prophylactic central lymph node (CLN) dissection or lateral lymph node (LLN) dissections to prevent metastasis is still controversial. This study aimed to retrospectively investigate the risk factors of LLN metastasis in clinical lymph node-negative (cN0) PTC patients.MethodsWe retrospectively studied 783 lymph node-negative (cN0) PTC patients who underwent total thyroidectomy plus CLN dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
5
27
1
Order By: Relevance
“…It was reported that multifocality increases the risk of CLNM ( 44 ). However, the role of multifocality in LLNM remains a topic of debate ( 43 , 45 ). Our results showed that patients with CLNM have more contralateral occult PTC but no significant relationship between LLNM and contralateral occult PTC.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that multifocality increases the risk of CLNM ( 44 ). However, the role of multifocality in LLNM remains a topic of debate ( 43 , 45 ). Our results showed that patients with CLNM have more contralateral occult PTC but no significant relationship between LLNM and contralateral occult PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In the right paratracheal basins, the superficial nodes anterior to the right recurrent laryngeal nerve were labeled as paratracheal lymph nodes in order to distinguish these from LN-prRLN12 The right central lymph nodes (rCLN) excluding the LN-prRLN refer to the group of Delphian, pretracheal, and paratracheal lymph nodes collectively. The surgical procedure was described in our previous study 16. After thyroid lobectomy, we subdivided the right central compartment into Delphian, pretracheal, paratracheal, and LN-prRLN groups depending on the anatomical position12 Four subgroups were removed and labeled sequentially, and then immediately sent for intraoperative frozen section examination.…”
Section: Methodsmentioning
confidence: 99%
“…Thyroid cancers (TC) are the most MBSJHS; 6(1), 2020 important diseases of the thyroid gland. İt is the most prevailing malignant tumor of the endocrine system (Hu et al, 2018). İt constitutes approximately 1% of all human malignancies and is the main cause of mortality among endocrine tumor-related deaths (Are & Shaha, 2006) İn 2010, Jemal et al reported 44700 new cases of thyroid cancers per year, worldwide, and 1700 deaths annually due to thyroid cancer (Jemal, Siegel, Xu, & Ward, 2010) Annual increase of 5.3% in TC incidence was reported by Magreni et al in 2015(Magreni, Bann, Schubart, & Goldenberg, 2015.…”
Section: Introductionmentioning
confidence: 99%